Strategies for Improving the use of Electronic Teaching and Learning(E-Learning) for Vocational Education in Tertiary Institutions of Anambra State-Nigeria - Azubuike, Ozioma C.; Offordile, S. (Richtmann Publishing, 2011)
The paper identified the strategies for improving the use of electronic teaching and learning of vocational educationcourses(agricultural science and home economics) in tertiary institutions of Anambra State. Simple random sampling was usedin selecting 30 lecturers and 150 students of agricultural science and Home Economics education. The questionnaire was theinstrument used for data collection. The data collected were analysed using mean and frequency counts. The findings of thestudy revealed that most schools lacks some of the e-learning devices and the problems facing the use of e-learning network inteaching includes poor power supply, financial problems, low computer literacy level, low quality and expensive nature of VASTconnections etc. The strategies that could be adopted to improve the use of electronic teaching and learning includes amongstothers training of teachers in ICT, allocation of more fund for e-learning, schools to source out fund, and telephone lines to bedigitalized.